Sperm maturation and male tactic‐specific differences in ejaculates in the plainfin midshipman fish Porichthys notatus - Jessica S. Miller; Aneesh P.H. Bose; John L. Fitzpatrick; Sigal Balshine (Journal of Fish Biology, 2019)
Using the plainfin midshipman fish Porichthys notatus , a species with alternative reproductive tactics (ARTs), we investigated how sperm maturation shapes sperm competitive abilities. We compared sperm performance and morphology before and after final sperm maturation by sampling sperm from the testes and stripped ejaculates of guarders and sneakers. In accordance with sperm competition risk theory, ejaculates from sneaker males had three times as much sperm as ejaculates from guarder males and sneaker males produced faster swimming sperm than guarder males, but this was only the case after final sperm maturation had occurred. Additionally, fully mature sperm found in ejaculates had larger heads and midpieces than sperm found in the testes. These results emphasize the important role played by non‐sperm components of an ejaculate in mediating sperm performance and potentially also morphology.